Are Starting Wages Reduced by an Insurance Premium for Preventing Wage Decline? Testing the Prediction of Harris and Holmstrom (1982) - Joop Hartog; Pedro Raposo (Institute for the Study of Labor (IZA), 2015)
In the model of Harris and Holmstrom (1982) workers pay an insurance premium to prevent a wage decline. As employers are unable to assess the ability of a labour market entrant, they would offer a wage equal to expected productivity of the worker's category and adjust it with unfolding information on true individual productivity. Workers are willing to accept a reduction in starting wage to prevent a reduction in their wage when their productivity is revealed to be below the expected value for their category. While Harris and Holmstrom indicate crystal clear how the prediction can be tested, their prescription has never been applied. Using Portuguese data covering virtually the entire labour force, we find that the prediction is unequivocally rejected. We interpret the results instead as confirmation of earlier results showing that workers are compensated for the financial risk of investing in an education.
Keywords: J31; D86; 330; risk premium; starting wages; unknown productivity; wage rigidity